2016
DOI: 10.3748/wjg.v22.i26.5936
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of short term outcome after liver transplantation: A review

Abstract: Liver transplantation represents a fundamental therapeutic solution to end-stage liver disease. The need for liver allografts has extended the set of criteria for organ acceptability, increasing the risk of adverse outcomes. Little is known about the early postoperative parameters that can be used as valid predictive indices for early graft function, retransplantation or surgical reintervention, secondary complications, long intensive care unit stay or death. In this review, we present state-of-the-art knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 118 publications
2
36
1
3
Order By: Relevance
“…The rate of graft loss was reported to be 26.1% for patients with EAD compared to 3.5% for patients without EAD. In addition, EAD is associated with longer intensive care unit and hospital stay due to postoperative complications such as renal failure, severe bleeding, and septic infection, which profoundly compromised graft and patient survival . In this study, EAD occurred in 29%, which is compatible with reported incidences of 18.3%‐36.3% .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The rate of graft loss was reported to be 26.1% for patients with EAD compared to 3.5% for patients without EAD. In addition, EAD is associated with longer intensive care unit and hospital stay due to postoperative complications such as renal failure, severe bleeding, and septic infection, which profoundly compromised graft and patient survival . In this study, EAD occurred in 29%, which is compatible with reported incidences of 18.3%‐36.3% .…”
Section: Discussionsupporting
confidence: 86%
“…We investigated an association between lactate clearance and occurrence of EAD, because several studies have validated the accuracy and usefulness of EAD criteria introduced by Olthoff, et al in 2010 to predict liver transplant outcomes . It is well known that EAD was associated with early morbidity and mortality following LT . Olthoff reported that 18.8% of the recipients with EAD died, whereas only 1.8% without EAD died.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, organs at high risk for IRI, when put into recipients primed for ischaemic injury, can lead to a potentially catastrophic scenario. Understanding IRI is, therefore, critical to success in liver transplantation …”
Section: Introductionmentioning
confidence: 99%
“…Understanding IRI is, therefore, critical to success in liver transplantation. 6 Liver IRI involves many cellular compartments. Liver sinusoidal endothelial cells and hepatocytes are targets of IRI-induced cell death.Early IRI-induced cell death is a result of metabolic disturbances and ATP depletion.…”
mentioning
confidence: 99%
“…У пациентов второй группы вено венозная гемодиафильтрация с ультрафильтрацией проводилась в качестве подготовки к реконструк ции веновенозного анастомоза. Развитие обрати мой ранней дисфункции трансплантата (по кри териям Olthoff) было отмечено у трех пациентов (11,5%) второй группы с использованием ВВОШ (в одном случае -АЛТ более 2000 Ед/л в течение первых 7 суток после ОТП; в двух случаях -МНО > 1,6 на 7е сутки после ОТП) [13]. В первой группе не отмечалось хирургических осложнений.…”
Section: результаты и обсуждениеunclassified